Peranan Emotional Spritual Quotient (ESQ) Dalam Doing Theology - Obet Nego Nego; Debby Christ Mondolu (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2016)
Dalam berteologi, Allah adalah sumber teologi, pokok teologi dan tujuan teologi. Dalam hal ini, Allah membuat manusia mempelajari-Nya di dalam Alkitab (Sola Scriptura), dan Roh Kudus yang menyingkapkan kebenaran-Nya sehingga menimbulkan iman di dalam diri umat-Nya (Sola Fide) kepada Allah dan kebenaran-Nya yang final, yaitu Tuhan Yesus Kristus saja (Sola Christo). Akhirnya, memimpin umat-Nya kepada diri-Nya sendiri dan demi kemuliaan nama Allah (Soli Deo Gloria). Dalam karya tulis memandang prinsip-prinsip dalam konsep Emotional Spiritual Quotient (ESQ) penting untuk diintegrasikan ke dalam doing theology atau berteologi. Dalam upaya mensinergiskan kecerdasan intelektual, emosi dan spiritual dalam berteologi yang teosentris, di mana kecerdasan spiritual (SQ) menjadi pusat kecerdasan. In theology, God is the source of theology, theology and the aim of theology. In this case, God made people study Him in the Bible (Sola Scriptura), and the Holy Spirit who revealed His truth so as to cause faith in His people (Sola Fide) in God and His final truth, namely God Jesus Christ alone (Sola Christo). Finally, leading His people to Himself and for the glory of the name of God (Soli Deo Gloria). In writing, the principles in the concept of Emotional Spiritual Quotient (ESQ) are important to be integrated into doing theology or doing theology. In an effort to synergize intellectual, emotional and spiritual intelligence in a theocentric theology, where spiritual intelligence (SQ) becomes the center of intelligence.